AXIOLOGICAL ORIENTATION AS A FORMATION FACTOR OF GENDER TOLERANCE IN STUDENT-AGE POPULATION - PILETSKA, LIUBOMYRA; DOBROVOLSKA , VITALIIA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
In the article, we carried out a theoretical analysis of gender tolerance concept and determined external and internal factors of its formation. There were distinguished the levels of our research concept: high, average and low; listed the main principles of gender tolerance, proposed the structure that includes four components: cognitive, emotional, behavioral, axiological; defined the characteristic features that merge in tolerant person. Axiological orientations are inner factors of gender tolerance formation that include instructions, beliefs, needs, objectives, motives, ideals, affirmations and values. The listed components have been grouped into three blocks: cognitive, motivational, operational, and distinguished the indicators of gender tolerance. We have emphasized the importance of study of psychological gender of personality, values, affirmations and beliefs, degree of acceptance of gender stereotypes within the range of research problem that will advance the level of gender culture.